Pengaruh Status Sosial Ekonomi, Kompetensi, dan Physical Appearance Terhadap Waktu Tunggu Mencari Kerja Alumni Fakultas Ekonomi dan Bisnis Universitas Udayana - Anak Agung Bagus Putu Widanta; IW Wita Kesumajaya (Jurnal Ekonomi Pembangunan, 2019)
This study aims to comprehensively examine the effect of socioeconomic status, competence, and physical appearance and examine which variables are most influential on the waiting time for job search for FEB alumni. Primary data is used as the central estimation, with a sample of FEB Unud alumni in the last three years. Evaluation is done by using multiple linear regression models with independent variables in the form of dummy variables. The estimation results provide a comprehensive picture of the factors influencing the injury time of seeking a job. The alumni work so that this can be a reference for faculties, especially Faculty of Business at Uiversitas Udayana, in developing curriculum and improving learning at the faculty level to produce quality graduates/outputs and approaching market needs productive work. The study results can also be a reference for Universitas Udayana alumni to improve competence and provide an overview in entering the labor market, which is increasingly complex and wins fierce labor market competition.